Research on Ellipse-Based Transient Impact Source Localization Methodology for Ship Cabin Structure - Xiufeng Huang; Rongwu Xu; Wenjing Yu; Xuan Ming; Shiji Wu (Journal of Marine Science and Engineering, 2025)
This study explores the application of three localization methods in identifying transient impact sources in the ship cabin structure. These methods examined are based on energy curvature and cumulative error, time-reversed virtual focusing triangulation, and energy correlation localization. It presents an elliptical region-based transient impact source localization technique for the ship cabin structure. The center of the elliptical region is determined by calculating the arithmetic mean of the position coordinates obtained from three methods, and the long and short semi-axes of the ellipse are defined as three times the standard deviations in the horizontal and vertical directions, respectively, to construct an elliptical localization area for precise positioning. Experimental results indicate that the average error distance of this impact localization technique is 0.10 m, with the predicted position error of 22 impact points being 0 m. Among 15 impact points, 14 impact points have error distances ranging from 0 m to 0.40 m, while 1 impact point has an error distance of 1.08 m, primarily due to the weak connection between sensors and the ship cabin structure. The overall localization error of the ship cabin structure is low, meeting the required localization accuracy.